Profitable tree-based model for carbon stock and CO2 mitigation potential: A competitive deep plough of wheat-poplar and eucalyptus-poplar agroforestry systems in Tarai region of Uttarakhand - Pratibha Singh; Dr Anil Kumar Shankhwar; Uma Melkania (Indian Journal of Agroforestry, 2023)
The study was initiated with the desire to select the profitable business model under two agroforestry systems namely- Agri-Silvi agroforestry (Site 1- Populus deltoides + Triticum aestivum) and Silvi-Silvi mixed forestry (Site 2- Populus deltoides + Eucalyptus camaldulensis). The present investigation deals with the estimation of soil properties including soil carbon stock, above-ground biomass production and CO2 mitigation potential. Soil carbon stock was compared in Agri-Silvi and Silvi-Silvi agroforestry systems. Owing to favourable soil characteristics for the species in the Silvi-Silvi agroforestry system, the contribution of Agri-Silvi was more towards biomass production and CO2 mitigation potential as well. MAI indicated that the age of species have a direct impact on biomass production and thus have a positive effect on CO2 mitigation. The clear-cut conclusion derived about agroforestry as an opportunity to the landowner for the biggest directly net gain through biomass productivity and indirectly through carbon storage on per unit land area without compromising agricultural output.